2023
DOI: 10.1002/alz.13068
|View full text |Cite
|
Sign up to set email alerts
|

Altered limbic functional connectivity in individuals with subjective cognitive decline: Converging and diverging findings across Chinese and German cohorts

Abstract: INTRODUCTIONIt remains unclear whether functional brain networks are consistently altered in individuals with subjective cognitive decline (SCD) of diverse ethnic and cultural backgrounds and whether the network alterations are associated with an amyloid burden.METHODSCross‐sectional resting‐state functional magnetic resonance imaging connectivity (FC) and amyloid‐positron emission tomography (PET) data from the Chinese Sino Longitudinal Study on Cognitive Decline and German DZNE Longitudinal Cognitive Impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…However, our results revealed subtle increases in white matter changes in the preclinical stage of AD that were not detectable using conventional MRI, suggesting an innovative compensation mechanism in the early course of AD. A recently published study that included data from two large, independent, ongoing longitudinal observational studies showed consistently increased global connectivity of the limbic regions across the two SCD cohorts ( Jiang et al, 2023 ). The results showed significantly higher degree of connectivity values in the cingulate cortex, hippocampus, and amygdala in SCD in comparison with HC, which is frequently interpreted as a compensatory phenomenon ( Catani et al, 2013 ), suggesting that vulnerable brain regions aroused excessively increasing connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results revealed subtle increases in white matter changes in the preclinical stage of AD that were not detectable using conventional MRI, suggesting an innovative compensation mechanism in the early course of AD. A recently published study that included data from two large, independent, ongoing longitudinal observational studies showed consistently increased global connectivity of the limbic regions across the two SCD cohorts ( Jiang et al, 2023 ). The results showed significantly higher degree of connectivity values in the cingulate cortex, hippocampus, and amygdala in SCD in comparison with HC, which is frequently interpreted as a compensatory phenomenon ( Catani et al, 2013 ), suggesting that vulnerable brain regions aroused excessively increasing connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the sample was ethnically and sociodemographically rather homogenous, most likely owing to our recruiting strategy via memory clinics and newspaper advertisements. Further studies are needed to assess the generalizability of our findings to individuals from different ethnic and cultural backgrounds 73,74 .…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
“…It generally includes the amygdala, thalamus, hypothalamus, and hippocampus, as well as many functionally and anatomically related regions that are considered paralimbic structures, including the prefrontal-limbic system, anterior cingulate cortex, medial temporal lobe network, para hippocampal gyrus, olfactory lobe, and ventral tegmental area ( Onofrj et al, 2022 ). Considerable overlap of the limbic network with the DMN, SN, and CEN can be seen in the anatomical composition, and this overlap also reflects the functional associations between the networks ( Jiang X. et al, 2023 ). This contains most of the inflammation-involved brain regions, thus explaining the peripheral inflammation-mediated impairment of memory and learning, both of which are often used as important dimensions in evaluating cognition.…”
Section: Affected Brain Regions and Functional Networkmentioning
confidence: 99%